Differences in the outcomes of anterior versus posterior interbody fusion surgery of the lumbar spine: A propensity score-controlled cohort analysis of 10, 941 patients. Issue 5 (May 2015) - Huang, Kevin T.; Hazzard, Matthew; Thomas, Steven; Chagoya, Gustavo; Berg, Rand Wilcox Vanden; Adogwa, Owoicho; Bagley, Carlos A.; Isaacs, Robert; Gottfried, Oren N.; Lad, Shivanand P.
Abstract Few studies have measured outcome differences between the various available spinal fusion techniques. We compare long-term outcomes of anterior versus posterior lumbar interbody fusion. Using the MarketScan database (Truven Health Analytics, Ann Arbor, MI, USA) we selected patients ⩾18 years old who underwent lumbar fusion surgery from 2000–2009 using either approach. Exclusion criteria included circumferential fusion, and having less than 1 year of preoperative or less than 2 years of postoperative follow-up. Using an inverse probability-weighted propensity-score model we compared reoperation and 90 day complication rates, and postoperative health resource utilization of both approaches. A total of 10, 941 patients were identified. Of these, 7460 (68.2%) and 3481 (31.8%) underwent posterior and anterior interbody fusion, respectively. Anterior fusion patients had a higher 2 year reoperation rate (odds ratio 1.43, 95% confidence interval [CI]: 1.21–1.70, p < 0.0001), although differences became non-significant at maximum follow-up (p = 0.0877). The 90 day complication rate was 15.7%, with anterior fusion patients being more likely to experience complications (relative risk 1.24, 95%CI: 1.13–1.36, p < 0.0001). Anterior fusion patients also had greater levels of postoperative health utilization, surpassing posterior fusion patients by an average of $US7450 in total charges (95% CI: $4670–$10, 220, p < 0.0001). As currently practiced in the USA, anterior lumbar surgical approaches may be associated with higher postoperative morbidity and reoperation rates than posterior fusion approaches.